Hubungan Pengetahuan Dan Sikap Tentang Pemenuhan Nutrisi Dengan Proses Penyembuhan Luka Ibu Post Sectio Caesarea Di RSUD Leuwiliang Tahun 2021: The Relationship of Knowledge and Attitude about Nutrition Fulfillment with Post Sectio Caesarea Mothers’ Wound Healing Process at Leuwiliang Hospital In 2021 - Saputra, Yudi Yanto (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Sectio Caesarea delivery has a five times greater risk of complications than normal childbirth, one of the complications that is one of the causes of maternal death in Indonesia is caused by Post Sectio Caesarea wounds and several factors that affect the healing of Post Sectio Caesarea wounds in mothers’ include: the environment, tradition, socioeconomic, maternal condition, nutrition, handling of personnel and quality of wound care. This study aims to determine the relationship of knowledge and attitudes about nutritional fulfillment to the wound healing process in Leuwiliang Hospital. Methods: The research design used was descriptive analytic with cross sectional method on the population of all mothers post caesarean section, totaling 72 samples taken by simple random sampling technique. Results: Based on the results of statistical tests using the chi square test, the p-value (0.00) is below the value of (0.05), which means that there is a significant relationship between knowledge and attitude towards nutrition fulfillment and the wound healing process of post SC mothers at Leuwiliang Hospital. Discussion: The general conclusion is that the behavior of fulfilling good nutritional intake will be created if the mother has good knowledge, attitude, and motivation where this will affect the healing process of the surgical wound on the mother after the caesarean section.